Effectiveness of the Initial Escalation of Immunochemotherapy in Patients with High Risk MALT-Lymphoma: Pilot Study Results - AK Smol’yaninova; NG Gabeeva; SA Tatarnikova; AV Belyaeva; AM Kovrigina; EG Gemdzhyan; EE Zvonkov (Клиническая онкогематология)
Background. MALT-lymphoma is usually characterized with an indolent course. The factors underlying the effectiveness of the standard chemotherapy in patients with MALT-lymphomas include MALT-IPI risk group and a high SUVmax according to the results of positron emission tomography (PET). All well-known MALT-lymphoma risk factors indirectly indicate a high risk of transformation to large cell lymphoma. The search for an effective chemotherapy continues.